2015
DOI: 10.1590/1519-6984.02413
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammation and hematological response in Nile tilapia fed supplemented diet with natural extracts of propolis and Aloe barbadensis

Abstract: This study evaluated the acute inflammatory response induced by carrageenin in the swim bladder of Nile tilapia supplemented with the mixture of natural extracts of propolis and Aloe barbadensis (1:1) at a concentration of 0.5%, 1% and 2% in diet during 15 days. Thirty-six fish were distributed into four treatments with three replicates: fish supplemented with 0.5% of admix of extracts of propolis and Aloe (1:1) injected with 500 µg carrageenin; fish supplemented with 1% of admix of extracts of propolis and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Moreover, COX‐2 and PGDS1 are inducible enzymes involved in the synthesis of prostaglandins, the expression of which is limited to a few cell types, including acidophilic granulocytes (Gómez‐Abellán et al., 2015). The present results showed that the upregulated gene expression levels of the proinflammatory genes il‐1β and pgds1 in the HK in the carrageenin group at 1.5 hr and 3 hr, respectively, could be related to the release of mediators responsible for increased blood flow, vasodilation and vascular permeability in order to facilitate the migration of leucocytes from the systemic circulation to the locally inflamed area (Dotta et al., 2015; Iman et al., 2017; Martins et al., 2009; Ribas et al., 2016).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, COX‐2 and PGDS1 are inducible enzymes involved in the synthesis of prostaglandins, the expression of which is limited to a few cell types, including acidophilic granulocytes (Gómez‐Abellán et al., 2015). The present results showed that the upregulated gene expression levels of the proinflammatory genes il‐1β and pgds1 in the HK in the carrageenin group at 1.5 hr and 3 hr, respectively, could be related to the release of mediators responsible for increased blood flow, vasodilation and vascular permeability in order to facilitate the migration of leucocytes from the systemic circulation to the locally inflamed area (Dotta et al., 2015; Iman et al., 2017; Martins et al., 2009; Ribas et al., 2016).…”
Section: Discussionmentioning
confidence: 84%
“…The available reports on the acute inflammation induced by λ-carrageenin demonstrated that the swim bladder of tilapia (Oreochromis niloticus) and pacu (Piaractus mesopotamicus) displayed vascular congestion, leucocyte infiltration and oedema 3 hr after administration. Furthermore, the severity of these conditions in the inflamed area peaked at 24 hr post-administration (Dotta et al, 2015;Martins et al, 2006;Matushima & Mariano, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A chronic inflammatory lipid-depositing disease causes peripheral artery disease, coronary artery disease, and myocardial infarction (Gao and Liu 2017). A dysfunction of vessel endothelium can initiate plaques and lead to atherosclerosis (Dotta et al, 2015;Rajendran et al, 2013). Oxidative stress and inflammatory reactions are important risk factors for atherosclerosis progression (Steven et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2014; Dotta et al, 2014Dotta et al, , 2015Farias et al, 2016) can affect the innate immune response of fish, what makes phagocytic assays an important tool for the evaluation of fish immunocompetence. However, few are the information regarding phagocytosis in Neotropical species (Jensch-Junior et al, 2006;Dias et al, 2011;Nunes et al, 2014;Farias et al, 2016).…”
Section: Introductionmentioning
confidence: 99%